Differences In The Effectiveness Of Brain Exercises And Beapreation Therapy On Cognitive Function In Elderly In Bujel Village Kediri City In 2023 - Eva Dwi Ramayanti; Indah Jayani (Master of Public Health Program Universitas STRADA Indonesia, 2024)
Elderly or old age is the final stage in the human life cycle. Those in this age range will begin to experience degenerative decline in all body systems, one of which is cognitive function. Serious treatment efforts are needed to maintain cognitive function in the elderly in society. One way is by applying complementary therapy. One of them is by applying behavioral therapy and brain exercises. Both of these therapies are able to improve the brain for calculus, memory, concentration etc. This research aims to find out the differences between brain exercises and behavioral therapy on cognitive function in the elderly in the Bujel sub-district, Kediri City in 2023. The population in this study is 45 elderly people in the Bujel sub-district. The sample in the study was 25 people in group 1 with behavioral therapy treatment and 20 people in group 2 with brain exercises using the sampling method using the total population. The research design used was pre-experiment with a two group pre-posttest and post-posttest method. The instrument used is the Mini Mental State Examination (MMSE). Bivariate analysis uses the Wilcoxon and Mann Whitney tests. The results of the research. The statistics obtained are: in group 1: p 0.00 < 0.05. There is an influence of beapreasi therapy on cognitive function in the elderly in Bujel sub-district, Kediri City in 2023. Before carrying out beapreasi therapy, most respondents experienced a mild decline in cognitive function. Meanwhile, after undergoing behavioral therapy, the majority of respondents had normal cognitive function. In group 2, the Pv value was obtained: 0.005 so that Pv<a concluded that there was an influence of brain exercise on cognitive function in the elderly. After comparing the results in the two groups, the value Pv: 0.000 was obtained, it was concluded that Pv <a. There are differences in the effect of the two therapies on cognitive function in the elderly. Appreciation therapy is better at improving cognitive function in the elderly compared to brain exercises, although the difference is very minimal. These two therapies are able to improve brain function by providing proper exercise and oxygenation patterns to the brain. It is hoped that brain exercises and behavioral therapy can be carried out regularly by elderly people in the community.